The 33-day war Israel's war on Hezbollah in Lebanon and its consequences - Achcar, Gilbert; Warschawski, Michel (Saqi, 2007)
Provides an assessment of the Israel-Lebanon conflict. This work describes the popular basis of Hezbollah in Lebanon among the Shiites, and its relation to the country's other religious communities and political forces. It analyzes the regional roles of Syria, Iran and Hamas as well as the politics of US and Europe.